IMPLEMENTASI TEKNOLOGI FERMENTASI SUSU KEFIR PADA PETERNAKAN SAPI PERAH DI KOTA PAYAKUMBUH - Ferawati Ferawati; Erpomen Erpomen; Yulianti Fitri Kurnia; Reswati Reswati; Khalil Khalil (Jurnal Hilirisasi IPTEKS, 2018)
The program is conducted at Abe Farm Sari Bulan independent farm located in Sawah Padang, South Payakumbuh and Tapian Agam farm group in Koto Baru, Payobasuang, East Payakumbuh. The empowerment program aims to overcome the problem sales milk that are not optimal. Relatively short milk storage and can reduce nutrition and reduce the quality and selling price after storage. This problem can be overcome by several approaches, namely the learning method in the form of training and mentoring with the service team as a facilitator in solving problems. In this case, the empowerment program team implemented the making of kefir as a solution to the problems experienced by dairy farmers in Payakumbuh city. The purpose of this program are to increase farmers' knowledge about the diversity of milk processing, improve farmers' skills in making kefir and derivative products, increase the insight and motivation of farmers in developing dairy products that are directly marketed conventionally and online so that it has an impact on increasing farmers' income. The result of this program are to increase in farmers' income from the sale of fresh milk which was initially sold at Rp. 10,000/liter but after processing it into kefir the price reached Rp. 30,000/liter.